Ethnobotanical knowledge of the lay people of Blouberg area (Pedi tribe), Limpopo Province, South Africa - Mongalo, Nkoana Ishmael (J Ethnobiol Ethnomed, 2018)
BACKGROUND: Limpopo province, South Africa, has a rich plant diversity and is referred to as one of the hotspots areas within the country. The aim of the current work was to identify and document medicinal plant species used by the indigenous Pedi people of Blouberg area, Limpopo Province, South Africa. METHODS: A total of 40 informants which includes both traditional healers and medicinal plant sellers were randomly selected and asked about the plant species used in treatment of variety of infections using a structured questionnaire. Follow-up visits and various field walks were also used to identify and document various plant species used in Traditional medicine (TM). The interviews were carried out from April 2008 to June 2016 using indigenous language (Sehananwa). RESULTS: A total of 82 medicinal plants species belonging to 42 families have been collected, identified and documented. About 46.34% of the plant species were herbs, followed by trees (25.61%), shrubs (20.73%) and climbers (7.32%). The most used plant parts are roots and rhizomes (58.58%). Peltophorum africanum Sond revealed frequency index of greater than 70 and is used in combination with other plants species to treat various pathogenic infections. Most of the plant species reported are used in the treatment of sexually transmitted infections (24), management of HIV-AIDS (15) and stomach ache (14). Our informants indicated that the use of plant medicines in combinations is also applied to cure pathogenic infections. CONCLUSION: The current study demonstrate that the indigenous people of Blouberg area, Limpopo Province harbours an important information about the vegetation around them. The plant species are used in the treatment of various pathogenic infections, offers fruits as additional source of food and form integral part of other medicinal products that may in turn produce income.